Urgency Analysis of Development of Self-Discovery and Exploration (SDE) Integrated Low Level Organism Taxonomy Module to Improve 21st Century Skills - Adi Hartono; Ashar Hasairin; Diky Setya Diningrat (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2022)
21st-century skills are very important skills possessed by the younger generation in order to compete and successfully face challenges in the global era. One of the efforts to improve 21st Century Skills is to integrate the Discovery Learning model and the assignment of the IQF into the concept of an innovatively created interactive learning module in the form of Self-Discovery and Exploration (SDE). Therefore, this study aims to explore the potential need for developing SDE-based modules in the Taxonomy of Low-Level Organisms courses to improve students' 21st-century skills. This research includes Research and Development (RD) research using the ADDIE model. The essence of this research specifically focuses on the Analysis stage in the ADDIE model series. Data collection techniques using questionnaires and interviews. The findings were analyzed descriptively qualitatively with the Miles and Huberman approach. The results showed that the lecturers admitted to agreeing and supporting the development of the SDE module to improve the quality of teaching materials in the Lower Level Organism Taxonomy course, as many as 60.40% of students from the Department of Biology, Faculty of Mathematics and Natural Sciences, State University of Medan admitted that they needed to improve their twentieth century skills. 21 and as many as 94% of students in the major agreed to use the SDE-based Taxonomy of Low-Level Organisms module. Based on this, it can be concluded that the development of the SDE integrated Low Level Organism Taxonomy module is an important thing to do to improve students' 21st Century Skills.